Evaluating the seasonal changes in calcium concentration and distribution in apple fruit after application of different calcium fertilisation strategies - Wilsdorf, Robert Ernst (Stellenbosch : Stellenbosch University, 2011)
Thesis (MScAgric)--Stellenbosch University, 2011.